ANALYSIS AND EVALUATION OF PHOTOVOLTAIC GRID CONNECTED SYSTEM IN PALESTINE - BAZYAN, Amin; ASSI, Hiba; MALHIS, Sura (My University, 2019)
Abstract Investing of grid connected PV systems for many Palestinian utilities has spread widely due to the decreasing price of the PV components and the supportive governmental policies that encourages stakeholders to invest in the renewable energy sector. A number of schools, municipality buildings and private firms have also built such PV systems. A sample of 15 schools was chosen to be evaluated technically and economically. These systems are rated at a range of 6-35 kWp. Furthermore, the systems were technically evaluated by calculating the yield factor, capacity factor and the performance ratio, the resulted numbers were compared to reference values from other researches. Finally, the ten sites were evaluated economically using simple pay-back period and IRR. This paper deals with the problem of economical and performance evaluation of the solar photovoltaic systems, based on the available operation data measurements. The main goal is to find out the most significant cause-effect relationships between the available measured inputs and the output power of the system. The problem is not easy one, because quite often the available measurements are correlated and in addition, they have an indirect influence on the final output of the system - the output power. The resulted data varied from one school to another, some sites had a good average values while others were far below the expected range. The main causes of these problems will be discussed specifically in the second part of our research. We will explain them from policy, behavior and technical points of view.